Adhesive as well as preparation method and application thereof
By using fluorine-containing anhydride as a curing agent, combined with epoxidized polybutadiene and maleimide resin, the problems of high dielectric loss, fragility and uneven appearance of the material in the prior art are solved, and the uniformity, mechanical properties and heat resistance of the material are improved, meeting the application needs in the field of high frequency and high speed.
Patent Information
- Application Number
- CN202411752985.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-28
AI Technical Summary
In the prior art, maleimide resin has a large dielectric loss in high-frequency and high-speed signal transmission applications, and the curing products are fragile, making it difficult to meet the toughness and processing requirements of the material. At the same time, epoxidized polybutadiene cannot be cured by active hydrogen curing agents, resulting in uneven appearance and poor mechanical properties.
Fluoroic anhydride is used as a curing agent, combined with epoxidized polybutadiene and maleimide resin, to achieve the improvement of the uniformity and mechanical properties of the material through efficient curing.
It significantly improves the appearance uniformity, mechanical properties and heat resistance of the material, reduces dielectric loss, and meets the application requirements in the field of high-frequency and high-speed.
Smart Images

Figure BDA0005165463220000031 
Figure BDA0005165463220000032 
Figure BDA0005165463220000051
Abstract
Description
Technical Field
[0001] The present invention relates to the field of materials, and more specifically, to an adhesive and a preparation method and application thereof. Background Art
[0002] As one of the key materials in the semiconductor field, the advent of the AI era has put forward more stringent requirements on the various properties of packaging substrate materials. The application scenarios of medium-high frequency and high-speed signal transmission require it to have low dielectric loss. Maleimide resin has good curing reactivity, and the imide ring generated after curing and cross-linking has the advantages of high temperature resistance and high glass transition temperature. Therefore, maleimide resin is widely used in the preparation of packaging substrate materials. However, due to the high polarity of maleimide resin, the dielectric loss of packaging substrate materials is relatively large, which is difficult to meet the application requirements of high frequency and high speed. At the same time, the cured product of maleimide resin is very brittle and its toughness is seriously insufficient, which leads to a significant increase in processing difficulty. Therefore, it is necessary to add a toughening agent to modify the maleimide resin. Due to its extremely low dielectric loss and good toughness, hydrocarbon resin has been often used in combination with maleimide resin in recent years to modify the packaging substrate material, reduce its dielectric loss, and improve the toughness of the product. However, hydrocarbon resins have low chemical activity and are difficult to cure and cross-link, which can easily lead to a series of problems such as poor mechanical properties of the material, low glass transition temperature, and uneven appearance.
[0003] Epoxidized polybutadiene is a modified hydrocarbon resin, which is prepared by oxidizing some double bonds in polybutadiene into epoxy groups. In use, hydroxyl groups and amines are usually added as curing agents to cure the epoxy groups in epoxidized polybutadiene. However, in fact, the epoxy groups in epoxidized polybutadiene are different from traditional epoxy resins and cannot be cured by active hydrogen curing agents. Therefore, in the existing solution, since epoxidized polybutadiene cannot be cured, it flows out at high temperature and has an uneven appearance, which is difficult to be accepted by downstream customers. Summary of the invention
[0004] The present invention aims to overcome at least one defect (shortcoming) of the above-mentioned prior art, provide an adhesive and a preparation method and application thereof, and improve the appearance uniformity of the material.
[0005] The technical solution adopted by the present invention is to provide an adhesive comprising the following components in parts by weight:
[0006] 100-150 parts of maleimide resin;
[0007] Epoxidized polybutadiene 60-100 parts;
[0008] 10-30 parts of fluorinated anhydride;
[0009] 15-30 parts of cross-linking agent;
[0010] Initiator 0.5-1 part;
[0011] 300-460 parts of filler;
[0012] 375-580 parts of solvent.
[0013] In the technical solution, the maleimide resin, as the main component of the adhesive material, has a large number of imide rings, which can give the material prepared by using it a higher glass transition temperature, thereby greatly improving the heat resistance and reliability of the material prepared by the present invention. And after the maleimide resin is modified with epoxidized polybutadiene, the toughness of the material can be improved and the dielectric loss of the material can be reduced.
[0014] Furthermore, the use of epoxidized polybutadiene as the hydrocarbon resin for modifying the maleimide resin solves the problem that ordinary hydrocarbon resins are difficult to cure and crosslink due to their chemical inertness, and also avoids the problems of poor mechanical properties, low glass transition temperature, and uneven appearance caused by the difficulty in curing.
[0015] Furthermore, by selecting fluorinated anhydride as a curing agent, efficient and sufficient curing of epoxidized polybutadiene is achieved, the uniformity of the material is greatly improved, and the material has good appearance, mechanical properties and heat resistance, avoiding the problem that the common epoxy curing agents of hydroxyl and amine are difficult to cure the epoxy groups in epoxidized polybutadiene and the uneven appearance occurs. And due to the efficient curing effect on epoxidized polybutadiene, the modification effect of epoxidized polybutadiene on maleimide resin is enhanced, thereby ensuring the toughening effect of epoxidized polybutadiene on maleimide resin, and further enhancing the mechanical properties of the material prepared by the adhesive. That is, the present invention greatly improves the curing efficiency through the dual guarantee of selecting epoxidized polybutadiene and fluorinated anhydride, and ensures that the material has excellent mechanical properties and uniform appearance.
[0016] In some embodiments, the fluorine-containing anhydride is one or a mixture of two or more of hexafluoroglutaric anhydride, tetrafluorobenzoic anhydride, and hexafluoroisopropylphthalic anhydride.
[0017] In some embodiments, the maleimide resin is selected from one or a mixture of two or more of N,N'-(4,4'-methylenediphenyl)bismaleimide, N,N'-m-phenylene bismaleimide, 2,2'-bis[4-(4-maleimidophenoxy)phenyl]propane, bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, 1,1-(4-methyl-1,3-phenylene)di-1H-pyrrole-2,5-dione, and polyphenylmethane maleimide.
[0018] In some embodiments, the structural formula of the polyphenylmethane maleimide is:
[0019]
[0020] Among them, n=1-5.
[0021] In some embodiments, the crosslinking agent is one or a mixture of two or more of pentaerythritol triacrylate, triallyl 1,3,5-cyanurate, trimethylolpropane trimethacrylate, tripropylene glycol diacrylate, and triallyl isocyanurate.
[0022] In some embodiments, the initiator is one or a mixture of two or more of azobisisobutyronitrile (AIBN), dibenzoyl peroxide (BPO), dicumyl peroxide (DCP), and 2,4-di-tert-butylcumyl peroxide (BIBP).
[0023] In some embodiments, the epoxidized polybutadiene has the structural formula:
[0024]
[0025] Among them, a+b+c+d=32-92, a+b=4-23, c+d=28-80.
[0026] In some embodiments, the filler is one or a mixture of two or more of vinyl surface-modified silica, epoxy surface-modified silica and amine surface-modified silica.
[0027] In some embodiments, the solvent is one or a mixture of two or more of cyclohexanone (CYC), methyl ethyl ketone (MEK), acetone (ACE), tetrahydrofuran (THF), dimethylformamide (DMF), ethylene glycol methyl ether (MCS), and propylene glycol methyl ether (PM).
[0028] Another object of the present invention is to provide a method for preparing any of the above-mentioned adhesives, comprising the following steps: adding maleimide resin and fluorine-containing anhydride to a solvent, mixing and dissolving, adding a crosslinking agent and epoxidized polybutadiene, mixing and dissolving, adding a filler, stirring, and adding an initiator.
[0029] In some embodiments, the solvent is first poured into a flask, and then the maleimide resin and the fluorinated anhydride are added, and fully dissolved by mechanical stirring. Then, the crosslinking agent and the epoxidized polybutadiene are added, and stirred to dissolve. Then, the filler is added, and the mechanical stirring is continued to disperse. Finally, the initiator is added to obtain the adhesive of the present invention.
[0030] Another object of the present invention is to provide a prepreg made of any of the above adhesives. In some embodiments, the raw materials for preparing the prepreg further include a reinforcing material.
[0031] Another object of the present invention is to provide a laminated board made of any of the prepregs described above. In some embodiments, the raw materials for preparing the laminated board further include copper foil.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] (1) The present invention uses anhydride curing agents to replace traditional hydroxyl and amine curing agents, achieving efficient curing of epoxidized polybutadiene, and solving the problems of uneven appearance caused by the inability of ordinary hydrocarbon resins to be cured due to chemical inertness and the difficulty of commonly used hydroxyl and amine epoxy curing agents to cure the epoxy groups in epoxidized polybutadiene. Since the present invention achieves efficient and sufficient curing of epoxidized polybutadiene, the uniformity of the material can be greatly improved, so that the material has good appearance, mechanical properties, heat resistance and reliability.
[0034] (2) The present invention selects fluorinated acid anhydride from the acid anhydride curing agent as the curing agent for epoxidized polybutadiene. Since no active hydrogen is introduced into the raw material and the cured product, the polarity of the material is greatly reduced. At the same time, a large number of fluorine atoms are introduced, which has the effect of increasing the free volume, and further reduces the dielectric loss of the material significantly, meeting the stringent requirements of the high-frequency and high-speed field on the dielectric properties of semiconductor packaging substrate materials.
[0035] (3) The present invention uses epoxidized polybutadiene to modify maleimide resin. Maleimide resin is used as the main component of the material, which ensures that the material has excellent heat resistance. At the same time, epoxidized polybutadiene can greatly reduce the dielectric loss of the material and improve the toughness of the material, meeting the requirements of the packaging carrier material on heat resistance, mechanical properties and dielectric properties, and improving its processability, which has broad application prospects.
[0036] (4) The method for preparing the low-dielectric and high-heat-resistant composite adhesive provided by the present invention is simple and easy to operate, which is conducive to realizing industrial production and reducing costs. DETAILED DESCRIPTION
[0037] In order to enable those skilled in the art to better understand the technical solution of the present application, the present application is further described in detail below in conjunction with specific embodiments.
[0038] The technical solution adopted by the present invention is to provide an adhesive comprising the following components in parts by weight:
[0039] 100-150 parts of maleimide resin;
[0040] Epoxidized polybutadiene 60-100 parts;
[0041] 10-30 parts of fluorinated anhydride;
[0042] 15-30 parts of cross-linking agent;
[0043] Initiator 0.5-1 part;
[0044] 300-460 parts of filler;
[0045] 375-580 parts of solvent.
[0046] In some embodiments, the fluorine-containing anhydride is one or a mixture of two or more of hexafluoroglutaric anhydride, tetrafluorobenzoic anhydride, and hexafluoroisopropylphthalic anhydride.
[0047] In some embodiments, the maleimide resin is selected from one or a mixture of two or more of N,N'-(4,4'-methylenediphenyl)bismaleimide, N,N'-m-phenylene bismaleimide, 2,2'-bis[4-(4-maleimidophenoxy)phenyl]propane, bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, 1,1-(4-methyl-1,3-phenylene)di-1H-pyrrole-2,5-dione, and polyphenylmethane maleimide.
[0048] In some embodiments, the structural formula of the polyphenylmethane maleimide is:
[0049]
[0050] Among them, n=1-5.
[0051] In some embodiments, the crosslinking agent is one or a mixture of two or more of pentaerythritol triacrylate, triallyl 1,3,5-cyanurate, trimethylolpropane trimethacrylate, tripropylene glycol diacrylate, and triallyl isocyanurate.
[0052] In some embodiments, the initiator is one or a mixture of two or more of azobisisobutyronitrile (AIBN), dibenzoyl peroxide (BPO), dicumyl peroxide (DCP), and 2,4-di-tert-butylcumyl peroxide (BIBP).
[0053] In some embodiments, the epoxidized polybutadiene has the structural formula:
[0054]
[0055] Among them, a+b+c+d=32-92, a+b=4-23, c+d=28-80.
[0056] In some embodiments, the filler is one or a mixture of two or more of vinyl surface-modified silica, epoxy surface-modified silica and amine surface-modified silica.
[0057] In some embodiments, the solvent is one or a mixture of two or more of cyclohexanone (CYC), methyl ethyl ketone (MEK), acetone (ACE), tetrahydrofuran (THF), dimethylformamide (DMF), ethylene glycol methyl ether (MCS), and propylene glycol methyl ether (PM).
[0058] Another object of the present invention is to provide a method for preparing any of the above-mentioned adhesives, comprising the following steps: adding maleimide resin and fluorine-containing anhydride to a solvent, mixing and dissolving, adding a crosslinking agent and epoxidized polybutadiene, mixing and dissolving, adding a filler, stirring, and adding an initiator.
[0059] In some embodiments, the solvent is first poured into a flask, and then the maleimide resin and the fluorinated anhydride are added, and fully dissolved by mechanical stirring. Then, the crosslinking agent and the epoxidized polybutadiene are added, and stirred to dissolve. Then, the filler is added, and the mechanical stirring is continued to disperse. Finally, the initiator is added to obtain the adhesive of the present invention.
[0060] Another object of the present invention is to provide a prepreg made of any of the above adhesives. In some embodiments, the raw materials for preparing the prepreg further include a reinforcing material.
[0061] Another object of the present invention is to provide a laminated board made of any of the prepregs described above. In some embodiments, the raw materials for preparing the laminated board further include copper foil.
[0062] Example 1
[0063] The present embodiment provides an adhesive, comprising the following components in parts by weight: 120 parts of polyphenylmethane maleimide, 60 parts of epoxidized polybutadiene PB4700, 15 parts of hexafluoroglutaric anhydride, 20 parts of pentaerythritol triacrylate, 300 parts of spherical silica, 0.5 parts of diisopropyl peroxide, 200 parts of cyclohexanone and 175 parts of butanone.
[0064] Example 2
[0065] The present embodiment provides an adhesive comprising the following components in parts by weight: 120 parts of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, 60 parts of epoxidized polybutadiene PB3600, 20 parts of tetrafluorophthalic anhydride, 15 parts of 1,3,5-triacyl cyanurate, 323 parts of spherical silica, 1 part of diisopropyl peroxide, 250 parts of cyclohexanone and 153 parts of butanone.
[0066] Example 3
[0067] The present embodiment provides an adhesive comprising the following components in parts by weight: 150 parts of N,N'-(4,4'-methylenediphenyl)bismaleimide, 90 parts of epoxidized polybutadiene PB4700, 30 parts of hexafluoroisopropylphthalic anhydride, 22.5 parts of trimethylolpropane trimethacrylate, 439 parts of spherical silica, 0.7 parts of diisopropyl peroxide, 300 parts of cyclohexanone and 248 parts of acetone.
[0068] Example 4
[0069] The present embodiment provides an adhesive comprising the following components in parts by weight: 150 parts of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, 90 parts of epoxidized polybutadiene PB3600, 30 parts of hexafluoroglutaric anhydride, 30 parts of tripropylene glycol diacrylate, 450 parts of spherical silica, 0.5 parts of azobisisobutyronitrile, 300 parts of cyclohexanone and 262 parts of butanone.
[0070] Example 5
[0071] The present embodiment provides an adhesive comprising the following components in parts by weight: 150 parts of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, 90 parts of epoxidized polybutadiene PB4700, 30 parts of hexafluoroisopropylphthalic anhydride, 30 parts of triallyl isocyanurate, 450 parts of spherical silica, 0.5 parts of diisopropyl peroxide, 300 parts of cyclohexanone and 263 parts of butanone.
[0072] Example 6
[0073] The present embodiment provides an adhesive, comprising the following components in parts by weight: 150 parts of polyphenylmethane maleimide, 70 parts of epoxidized polybutadiene PB3600, 25 parts of tetrafluorophthalic anhydride, 30 parts of 1,3,5-triallyl cyanurate, 413 parts of spherical silica, 1 part of dibenzoyl peroxide, 300 parts of cyclohexanone and 216 parts of acetone.
[0074] Example 7
[0075] The present embodiment provides an adhesive comprising the following components in parts by weight: 100 parts of N,N'-(4,4'-methylenediphenyl)bismaleimide, 90 parts of epoxidized polybutadiene PB3600, 20 parts of hexafluoroisopropylphthalic anhydride, 30 parts of triallyl isocyanurate, 360 parts of spherical silica, 0.5 parts of azobisisobutyronitrile, 250 parts of cyclohexanone and 200 parts of acetone.
[0076] Example 8
[0077] The present embodiment provides an adhesive comprising the following components in parts by weight: 100 parts of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, 90 parts of epoxidized polybutadiene PB4700, 30 parts of hexafluoroisopropylphthalic anhydride, 30 parts of triallyl isocyanurate, 375 parts of spherical silica, 0.5 parts of diisopropyl peroxide, 300 parts of cyclohexanone and 169 parts of butanone.
[0078] Example 9
[0079] The present embodiment provides an adhesive, comprising the following components in parts by weight: 150 parts of polyphenylmethane maleimide, 100 parts of epoxidized polybutadiene PB3600, 25 parts of tetrafluorophthalic anhydride, 30 parts of 1,3,5-triallyl cyanurate, 460 parts of spherical silica, 1 part of dibenzoyl peroxide, 300 parts of cyclohexanone and 280 parts of acetone.
[0080] Example 10
[0081] The present embodiment provides an adhesive comprising the following components in parts by weight: 100 parts of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, 90 parts of epoxidized polybutadiene PB4700, 10 parts of hexafluoroisopropylphthalic anhydride, 30 parts of triallyl isocyanurate, 345 parts of spherical silica, 0.5 parts of diisopropyl peroxide, 300 parts of cyclohexanone and 131 parts of butanone.
[0082] Embodiment 11
[0083] This embodiment provides a method for preparing an adhesive, which is used to prepare the adhesives provided in embodiments 1 to 10. The method comprises: firstly pouring a solvent into a flask, then adding a maleimide resin and a fluorine-containing acid anhydride, mechanically stirring for 1 hour at a speed of 500 rpm by an electric stirrer to dissolve, then adding a crosslinking agent and epoxidized polybutadiene, stirring to dissolve, adding a filler, continuing to mechanically stir for 2 hours at a speed of 1500 rpm by an electric stirrer to disperse, and finally adding an initiator to obtain the adhesive of the present invention.
[0084] Example 12
[0085] This embodiment provides a laminate, which is prepared using the adhesive provided in Embodiments 1 to 10.
[0086] Example 13
[0087] This embodiment provides a method for preparing a laminate, which is used to prepare the laminate provided in embodiment 12. The preparation method comprises:
[0088] 2116 glass fiber cloth (basic weight 105g / m 2) was immersed in the adhesive provided in Examples 1 to 10, and after being taken out, moved to a 200° C. oven and baked for 3.5 minutes to obtain a semi-cured sheet with an adhesive content of 50%.
[0089] 8 prepregs were stacked and covered with 18 micron electrolytic copper foil on both sides. They were placed on a vacuum press and set at a pressure of 35 kgf / cm 2 The laminate with a thickness of 0.85 mm was prepared by pressing for 3 hours at a temperature of 220°C.
[0090] Comparative Example 1
[0091] This comparative example provides an adhesive comprising the following components in parts by weight: 120 parts of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, 60 parts of epoxidized polybutadiene PB3600, 20 parts of phenolic resin, 15 parts of 1,3,5-triacyl cyanurate, 323 parts of spherical silica, 1 part of diisopropyl peroxide, 250 parts of cyclohexanone and 153 parts of butanone.
[0092] Comparative Example 2
[0093] This comparative example provides an adhesive, comprising the following components in parts by weight: 150 parts of N,N'-(4,4'-methylenediphenyl)bismaleimide, 90 parts of epoxidized polybutadiene PB4700, 22.5 parts of trimethylolpropane trimethacrylate, 394 parts of spherical silica, 0.7 parts of diisopropyl peroxide, 300 parts of cyclohexanone and 192 parts of butanone.
[0094] Comparative Example 3
[0095] This comparative example provides an adhesive comprising the following components in parts by weight: 150 parts of bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, 90 parts of epoxidized polybutadiene PB3600, 30 parts of 4,4'-diaminophenylsulfone, 30 parts of tripropylene glycol diacrylate, 405 parts of spherical silica, 0.5 parts of azobisisobutyronitrile, 300 parts of cyclohexanone and 206 parts of acetone.
[0096] Laminated boards were prepared respectively using the adhesives provided in Comparative Examples 1 to 3, and the preparation methods of the laminated boards were the same as the preparation method provided in Example 13.
[0097] The curing agents used in the adhesives of Examples 1 to 10 and Comparative Examples 1 to 3 are shown in Table 1. The curing agent herein refers to a component for curing epoxidized polybutadiene.
[0098] Table 1
[0099]
[0100]
[0101] The laminates prepared with the adhesives provided in Examples 1 to 10 and Comparative Examples 1 to 3 were subjected to the following tests:
[0102] (1) Peel off the laminate to remove the copper foil, and then visually inspect the material to see if it is uniform in appearance.
[0103] (2) The glass transition temperature of the laminate was measured using a DMA850 dynamic mechanical analyzer from TA. The test conditions were: 3°C / min, heating from 50°C to 350°C, frequency of 1 Hz, and deformation of 20 μm.
[0104] (3) The copper foil is removed from the laminate to obtain a laminate without copper foil. The dielectric constant Dk and dielectric loss Df are measured at a frequency of 10 GHz using a KEYSIGHT N5224B vector network analyzer from the United States.
[0105] The test results are shown in Table 2.
[0106] Table 2
[0107] Laminate Is the appearance uniform? Dielectric constant Dielectric loss Glass transition temperature(℃) Example 1 Ok 4.35 0.0066 286 Example 2 Ok 4.31 0.0062 289 Example 3 Ok 4.25 0.0056 268 Example 4 Ok 4.26 0.0058 265 Example 5 Ok 4.25 0.006 283 Example 6 Ok 4.36 0.0072 272 Example 7 Ok 4.21 0.0058 263 Example 8 Ok 4.20 0.0052 263 Example 9 Ok 4.24 0.0064 263 Example 10 Ok 4.23 0.0062 260 Comparative Example 1 NG 4.48 0.0125 265 Comparative Example 2 NG 4.41 0.0092 288 Comparative Example 3 NG 4.51 0.0132 275
[0108] From the test results in Table 2, it can be seen that the laminates prepared using the adhesives of Examples 1 to 10 have a uniform appearance, while the laminates corresponding to Comparative Examples 1 to 3 are all uneven in appearance. Moreover, the dielectric constants of the laminates corresponding to Examples 1 to 10 are all no more than 4.36, and the dielectric losses are all no more than 0.0072, while the dielectric constants of Comparative Examples 1 to 3 are all greater than 4.41, and the dielectric losses are all greater than 0.0092. Combined with the glass transition temperature, it can be seen that, in comparison, the laminates prepared by the adhesive of the present invention, while having the excellent properties of low dielectric, high glass transition temperature, and low dielectric loss, maintain an excellent uniform appearance, which is not only more beautiful, but also ensures good mechanical properties. The specific relevant principles are described as follows:
[0109] In recent years, hydrocarbon resins are often used to modify maleimide resins to reduce the dielectric loss of materials, but hydrocarbon resins have low chemical activity and are difficult to achieve curing and crosslinking. Epoxidized polybutadiene, as a modified hydrocarbon resin, is prepared based on the oxidation of some double bonds in polybutadiene into epoxy groups. It has been reported that epoxidized polybutadiene and maleimide resin are used together to prepare copper clad laminate materials. However, these existing solutions all require the addition of hydroxyl and amine curing agents such as phenolic resins, 4,4'-diaminophenylsulfone, benzoxazine, etc. as curing agents to cure the epoxy groups in epoxidized polybutadiene, such as Comparative Examples 1-3. However, in fact, the epoxy groups in epoxidized polybutadiene are different from traditional epoxy resins and cannot be cured by active hydrogen curing agents.
[0110] Therefore, in the existing scheme, due to the epoxidized polybutadiene cannot be cured and cause high temperature phase separation to flow out, and the state of uneven appearance occurs, and also can cause a series of problems such as poor material mechanical properties, low glass transition temperature. In addition, in the existing scheme, due to the introduction of a large amount of active hydrogens such as hydroxyl or amino, the polarity is very large, resulting in a significant increase in the dielectric loss of the material, thereby limiting the application of the material in the field of high frequency and high speed. The present invention is directed to the above existing problems, while using epoxidized polybutadiene to modify maleimide resin to achieve toughening and reduce dielectric loss, by using fluorinated anhydride, achieving efficient and sufficient curing of epoxidized polybutadiene, preparing a low dielectric laminate material with uniform appearance, sufficient curing, and high reliability, and because epoxidized polybutadiene is fully cured, achieving a good toughening effect on maleimide resin, avoiding the processing difficulty problem of material due to brittleness.
[0111] In addition, fluorinated anhydride, as a fluorinated compound, has been widely used in the preparation of low dielectric polyimide. Similarly, the present invention uses fluorinated anhydride as a curing agent, and the introduction of a large number of fluorine atoms also achieves the effect of increasing free volume, thereby further significantly reducing the dielectric loss of the material. In addition, since maleimide resin has a large number of imide rings, the material is given a higher glass transition temperature, which can significantly improve the heat resistance and reliability of the material prepared by the present invention. In summary, the laminate material provided by the present invention can meet its stringent requirements in application and processing as a semiconductor packaging carrier material due to its uniform appearance and excellent dielectric properties, mechanical properties, reliability, heat resistance, processing performance and other excellent comprehensive properties, and is applied to high-frequency and high-speed communication fields.
[0112] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. An adhesive, characterized in that: The composition comprises the following components in parts by weight: 100-150 parts of maleimide resin; Epoxidized polybutadiene 60-100 parts; 10-30 parts of fluorinated anhydride; 15-30 parts of cross-linking agent; Initiator 0.5-1 part; 300-460 parts of filler; 375-580 parts of solvent.
2. The adhesive according to claim 1, characterized in that The fluorine-containing anhydride is one of hexafluoroglutaric anhydride, tetrafluorophthalic anhydride, and hexafluoroisopropylphthalic anhydride, or a mixture of two or more thereof.
3. The adhesive according to claim 1, characterized in that The maleimide resin is selected from one or a mixture of two or more of N,N'-(4,4'-methylenediphenyl)bismaleimide, N,N'-m-phenylenebismaleimide, 2,2'-bis[4-(4-maleimidophenoxy)phenyl]propane, bis(3-ethyl-5-methyl-4-maleimidophenyl)methane, 1,1-(4-methyl-1,3-phenylene)di-1H-pyrrole-2,5-dione, and polyphenylmethane maleimide.
4. The adhesive according to claim 3, characterized in that The structural formula of the polyphenylmethane maleimide is: Among them, n=1-5.
5. The adhesive according to claim 1, characterized in that The crosslinking agent is one of pentaerythritol triacrylate, 1,3,5-triallyl cyanurate, trimethylolpropane trimethacrylate, tripropylene glycol diacrylate, and triallyl isocyanurate, or a mixture of two or more thereof.
6. The adhesive according to claim 1, characterized in that: The initiator is one of azobisisobutyronitrile, dibenzoyl peroxide, dicumyl peroxide, and 2,4-di-tert-butylcumyl peroxide, or a mixture of two or more thereof.
7. The adhesive according to any one of claims 1 to 6, characterized in that: The structural formula of the epoxidized polybutadiene is: Among them, a+b+c+d=32-92, a+b=4-23, c+d=28-80.
8. A method for preparing the adhesive according to any one of claims 1 to 7, characterized in that: The following steps are involved: Add maleimide resin and fluorine-containing acid anhydride into solvent, mix and dissolve, add crosslinking agent and epoxidized polybutadiene, mix and dissolve, add filler, stir, and add initiator.
9. A prepreg made of the adhesive according to any one of claims 1 to 7.
10. A laminated board made using the prepreg according to claim 9.
Citation Information
Cited By
Preparation method of modified liquid hydrocarbon polymer, resin composition and application thereof
CN120647835A